2004
DOI: 10.1128/mcb.24.21.9339-9350.2004
|View full text |Cite
|
Sign up to set email alerts
|

BRUCE, a Giant E2/E3 Ubiquitin Ligase and Inhibitor of Apoptosis Protein of the trans-Golgi Network, Is Required for Normal Placenta Development and Mouse Survival

Abstract: BRUCE is a highly conserved 528-kDa peripheral membrane protein of the trans-Golgi network. Owing to the presence of an N-terminal single baculovirus inhibitor repeat, BRUCE functions as an inhibitor of apoptosis protein and blocks apoptosis when overexpressed. In addition, due to the presence of a C-terminal ubiquitin-conjugating domain, BRUCE can covalently attach ubiquitin to substrates. Here we report the generation and characterization of BRUCE-deficient mice. Complete inactivation of the BRUCE gene resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 27 publications
1
68
0
Order By: Relevance
“…We were especially interested in the upregulation of BRUCE mRNA by PGF2a, given the reported role for BRUCE in inhibition of apoptosis. 18,21 Therefore, we confirmed by realtime RT-PCR that BRUCE mRNA expression increases approximately twofold in response to PGF2a treatment (Figure 2b). To determine whether PGF2a treatment increases BRUCE protein expression, we utilized flow cytometry ( Figure 2c) and determined that following 6 h of PGF2a treatment, the proportion of BRUCE þ muscle cells increased 9.8±0.9% relative to vehicle (n ¼ 4, Po0.001).…”
Section: Pgf2asupporting
confidence: 63%
See 2 more Smart Citations
“…We were especially interested in the upregulation of BRUCE mRNA by PGF2a, given the reported role for BRUCE in inhibition of apoptosis. 18,21 Therefore, we confirmed by realtime RT-PCR that BRUCE mRNA expression increases approximately twofold in response to PGF2a treatment (Figure 2b). To determine whether PGF2a treatment increases BRUCE protein expression, we utilized flow cytometry ( Figure 2c) and determined that following 6 h of PGF2a treatment, the proportion of BRUCE þ muscle cells increased 9.8±0.9% relative to vehicle (n ¼ 4, Po0.001).…”
Section: Pgf2asupporting
confidence: 63%
“…37 Multiple groups have generated BRUCE-deficient mice, and all mice are embryonic lethal. [20][21][22] However, whether embryonic lethality associated with loss of BRUCE function is caused by an increase in apoptosis is unclear. Ren et al 22 reported the abundance of apoptotic cells in the placenta and yolk sac in mice lacking the C-terminal half of BRUCE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Complete inactivation of the Bruce gene in mice results in perinatal lethality and growth deficiencies. 15 In Drosophila, overexpression of dBruce can inhibit cell death induced by the proapoptotic Smac analogs Reaper and Grim. 14 Several lines of evidence show that the Apollon can protect cells against apoptosis and functions as an IAP by binding the active caspases via its single BIR domain.…”
Section: Introductionmentioning
confidence: 99%
“…35 Several groups have reported deleting BRUCE in mice. [36][37][38] While all agree that deletion of BRUCE results in embryonic lethality, its exact role remains controversial, with suggested activities including preventing p53 activation, 38 directly binding to both unprocessed and mature Smac/DIABLO and both pro-and processed caspase 9, and targeting them for degradation. 36,39,40 Survivin is a BIR containing protein that acts together with INCENP and Aurora kinase B in a complex required for chromosome segregation and cytokinesis during mitosis.…”
mentioning
confidence: 99%